2009
DOI: 10.1038/cgt.2009.39
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells engineered to secrete anti-GITR antibodies are effective adjuvants to dendritic cell-based immunotherapy

Abstract: A number of monoclonal antibodies (mAbs) have been studied for their ability to enhance immune responses. Although these antibodies are effective in pre-clinical and clinical studies, they are costly and have occasionally been associated with adverse effects such as autoimmunity and cytokine storm. Numerous studies have shown that treatment of mice with an agonistic mAb, clone DTA-1, targeting murine glucocorticoid-induced tumor necrosis factor receptor (GITR) results in enhanced immune responses in tumor-bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 48 publications
0
45
0
Order By: Relevance
“…Our laboratory has chosen RNA transfection for loading DCs with TAAs because of the many advantages of this approach over other methods of antigen loading that have routinely been used both experimentally and in DC-based clinic immunotherapy trials in subjects with cancer (12)(13)(14)(15)(16)(17)(18). This method relies on the DC translating the transfected RNAs into the TAA proteins, which are then degraded into peptides in the cytoplasm by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has chosen RNA transfection for loading DCs with TAAs because of the many advantages of this approach over other methods of antigen loading that have routinely been used both experimentally and in DC-based clinic immunotherapy trials in subjects with cancer (12)(13)(14)(15)(16)(17)(18). This method relies on the DC translating the transfected RNAs into the TAA proteins, which are then degraded into peptides in the cytoplasm by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of mice with an agonistic anti-GITR mAb alone enhances anti-viral and anti-tumor immune responses [10,11,[20][21][22][23][24]. When combined with immunization against melanoma-related antigens, we and others have found that agonistic anti-GITR mAb-treated mice demonstrated increased tumor antigen-specific T cell responses and protective tumor immunity [10,17,25]. These data indicate that systemic treatment with agonistic anti-GITR mAb, alone or as an adjunct to active immunization, increases the ability to overcome immune tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Generation and electroporation of murine DCs-DCs were generated from bone marrow precursors as described previously [17] in RPMI-5% FCS with GM-CSF (15 ng/ml) and IL-4 (10 ng/ml). GITR expression on bone marrow-derived DCs was low to negative (mature DCs ≤ 15-18% and immature DCs ≤ 10-12%, data not shown).…”
Section: Murine In Vivo Experimentsmentioning
confidence: 99%
See 2 more Smart Citations